Sushi Nation - Kocienda, Genevieve (NewYork Cambridge University, 2014)
Living off the sea has shaped the lives and professions of the Japanese people. Come explore the traditions and the changing world of ama divers, tuna fishermen, sushi knife makers, and sushi chefs.
Cambridge Discovery Education Interactive Readers are the next generation of graded readers - captivating topics, high-impact video, and interactive exercises designed to motivate and engage.
Glossary, Contents.
Keywords: English language; Food; Pre-Intermediate Level